Impoliteness Strategies and Gender Differences among Disney Modern Protagonists - Benabdellah, Fatima Zohra (European Journal of Multidisciplinary Studies, 2018)
Disney Animation industry has grown, over the years, as a powerful producer of youth media and generator of visual culture. Its animation films break into the world’s living-room screens and mesmerize young spectators with a fantasy world full of life, magic and colors, where love and happiness are everlasting. The genre of anime, through a series of images, creates a link between the child and characters; a desirable image of self-seeing oneself reflected and experienced by the story characters, mediates how the spectator wants to be seen by others. Hence, these fe/male protagonists cross from being plain characters to become “Role Models” promoting impolite social norms and gender performances through their discursive practices. This research is concerned with the study of how modern fe/male highest grossing Disney characters use language to shape social identities through their impolite discourse and gender behaviors; By drawing on Culpeper’s (2010) ‘Model of Impoliteness Formulae’. The results of the model will be further examined with language and gender theories in order to uncover how both genders (females and males) use impoliteness strategies to re/produce and maintain their power relations. Keywords: Disney, role models, impoliteness, gender, power
Keywords: Disney, role models, impoliteness, gender, power